Histoire(s) du cinéma = Geschichte(n) des Kinos - Theweleit, Klaus 1942- (Suhrkamp, 2009)
A philosophical and complex view of the history of film, presented in a non-linear, non-chronological narrative, as montage. The work was begun in the 1980's and presented chapter by chapter until completed in the late1990s. The end result is a collection of video essays on a century of filmmaking and films inherent connection to art, politics, music, literature and society.
Begleith. m.d.T.: Bei vollem Bewußtsein schwindlig gespielt / Klaus Theweleit
Bildformat 4:3
Orig.: Frankreich 1996
Enth. Booklet mit einem Essay von Klaus Theweleit
Keywords: Godard, Jean-Luc <1930-> -- Histoire(s) du cinéma; Geschichte; Film; Philosophie; Motion pictures -- History -- Philosophy; DVD-Video; DVD-Video discs; Documentary films; Experimental films